Thin-layer hydration method to prepare a green tea extract niosomal gel and its antioxidant performance - Chasanah U.; Mahmintari N.; Hidayah F.; El Maghfiroh F.A; Rahmasari D.; Weka Nugraheni R. (Sciendo, 2021)
This study aimed to prepare a niosomal gel of green tea (Camellia sinensis) extract containing catechins, mostly epigallocatechin-3-gallate (ECGC), as a potent antioxidant. Niosomes can increase EGCG's stability and penetration into the skin for a better therapeutic effect. Niosomes were prepared by a thin-layer hydration method, were evaluated for their vesicle shape, particle size, polydispersity index, zeta potential and entrapment efficiency, and then incorporated into gels using sodium alginate as a gelling agent. Three niosomal gel formulations were prepared with different concentrations of niosomes green tea extract. Afterwards, organoleptic properties, chemical and physical characteristics, antioxidant activity, and stability and irritability of the niosomal gels were investigated. The different concentrations of green tea extract had a significant effect on the physical characteristics, but not on the chemical ones. Its antioxidant activity was determined using the 1,1-diphenyl-2-picrylhydrazyl (DPPH) scavenging method. The 50% extract green tea niosomes gel showed the highest inhibition value (25.13%). The stability was determined by freeze-thaw and real-time methods; they showed a decrease in pH, but still within the pH range of skin. The irritability test used was the Hen's Egg Test-Chorioallantoic Membrane (HET-CAM) method, which showed no irritation for all formulas. In conclusion, 50% green tea extract niosomes gel results showed it to be the best formulation with optimal antioxidant results.